Adsorption and porosity study of Acacia catechu seed derived activated carbon - Mishra, Pawan Kumar; Ram, Anant; Subedi, Netra Prasad; Jha, Dhirendra; Gautam, Madhab (Rajarshi Janak University Research Journal, 2025)
Nowadays several biomasses based adsorbent materials are in practice. The activated carbon (AcC) shows efficient adsorption capacity. The pore size and surface morphology is essential for the best AcC that depends on the selection of activating agents. The aim of this study is to employ potassium Hydroxide (KOH) as a chemical activating agent for synthesizing AcC using Acacia catechu seeds through a carbonization process. Fourier-transform infrared spectroscopy (FTIR) was used to identify the functional groups present in carbonaceous materials while the X-ray diffraction (XRD) analysis was done for studying the crystalline nature of synthesized AcC. The surface morphology was studied with the help of image obtained from Field-Emission Electron Spectroscopy (FESEM). The iodine number (IN) and methylene blue number (MBN) for the sample activated with KOH (SACK-4) have been found to be 711.42 mg/g and 186.34 mg/g respectively which are much higher values in comparison to the corresponding numbers of non-activated sample (SACK-0), suggesting better adsorption performance of SACK-4. Furthermore, remarkable porosity has been achieved with SACK-4 that make it as a prominent candidate for different industrial and technical applications.